An enhancement of authentication and energy efficient clustering protocol for wireless sensor network / Ahmed Abdulhadi Jasim - Ahmed Abdulhadi , Jasim (2021)
Clustering is one of the popular techniques for Wireless Sensor Networks (WSNs) topology management. In each cluster, a leader is selected referred to as cluster head while the rest of the nodes in a cluster are referred to as cluster members. Clustering has been proven to be the most efficient approach in WSN. However, to realize the full benefit of clustering proper authentication and energy efficiency are needed to provide control to the WSN resources and prolonged network lifetime. Two of the main issues in implementing WSN clustering protocol are security issues related to authentication and energy efficiency issues. Therefore, in the first part of this thesis, the focus is given on how to overcome authentication and energy issues due to the problem of the security key and key length sharing at the base station. This can be done by enhancing the authentication of the Media Access Control (MAC) address and by utilizing the distance information and timestamp to detect attacks and reduces energy consumption, using a protocol called Secure and Energy-Efficient Data Aggregation method in clustering based on access control model (SEEDA). The proposed SEEDA protocol enhances the MAC address by utilizing a secret key and random timestamp in the verification process. The base station nodes also utilize the distance and timestamp between nodes to avoid delay in the network. The performance of the proposed SEEDA protocol is compared with SDA, SDAT, SDALFA, EESSDA, SDAACA, and EESDA, which is a widely used clustering protocol in the area of authentication. The simulation results show that the proposed SEEDA protocol outperforms the existing scheme with a 98.84% malicious nodes detection rate, 3.04 joules for energy consumption, the maximum delay of 0.038 seconds, and the resilient time of 0.054, 0.075 seconds with 8%,16% of malicious nodes affecting the network. Apart from looking at the authentication and energy issues, this thesis also focuses on another important energy efficiency issue, which is the hot spots problem. In the WSNs environment, the sensor nodes closer to the base station nodes will take on more forwarding tasks. This will result in a massive overhead of the sensor nodes, and these nodes will run out of power sooner than the others. It causes a breakdown of the nodes and a loss of communication between sensor nodes; this breakdown is called the hot spots problem. Therefore, in the second part of this thesis, the focus is given on how to reduce the hot spots problem and balance the energy consumption among nodes. This can be done by utilizing an unequal clustering in the WSNs is able to reduce the hot spots problem, using a protocol called Energy-Efficient Unequal Clustering protocol based on a Balanced energy method (EEUCB). The proposed EEUCB protocol utilizes an unequal clustering mechanism based on the competition radius, double cluster head selection that reduces the energy consumption of head nodes in the clusters are proposed, applied the sleep and awake mechanism, and the base station calculates the distance based on the closest and farthest nodes and divides this distance into four layers as opposed to depends only on the residual energy of sensor nodes and the distance from all the sensor nodes to the base station node for calculating the competition radius in the prior methods, and also to enhance the data transmission process between sensor nodes and cluster head nodes in the network. EEUCB is compared with UDCH, EEFUC, FLEACH, and LEACH by performing various simulations. The simulation results show that the proposed EEUCB clustering protocol has achieved 13.06%, 14.7%, 19.75%, and 57.75% lifetime improvements against LEACH, EEFUC, FLEACH, and UDCH, respectively.